Perancangan Key Performance Indicator pada Departemen Depo di PT. X dengan Metode DEMATEL - Hendrawan Sugiharto Putra (Jurnal Titra, 2022)
This study was conducted in a liner company, namely PT. X., particularly in the Depot Department. PT. X is a company engaged in the business of container rental and ship loading expeditions, The Depot Department serves customers directly and all container-related activities like stripping in, stripping out, stuffing in, and stuffing out. Depot Department already have three quality targets. Already has three quality goals that have been running for several years, however, it is felt that it is lacking to monitor the performance of the depot. Therefore, PT. X wants to maintain, improve and monitor the depot’s performance. To answer that need, we design new KPIs for the Depot Department through Business Model Canvas (BMC) and Decision-Making Trial and Evaluation Laboratory (DEMATEL). As a result, we found for new quality target proposals that are, serving the customer, finding empty containers, the availability of spare heavy equipment, the availability of spare thermal backup, these four quality goals also support the company's policy.